Androgen regulation of dendritic growth and retraction in the development of a sexually dimorphic spinal nucleus - Goldstein, LA (J Neurosci, 1990)
The spinal nucleus of the bulbocavernosus (SNB) is a sexually dimorphic group of motoneurons whose development and maintenance are under androgenic control. Exposure to androgens early in development permanently alters SNB motoneuron number and soma size; in adulthood, androgens regulate dendritic and synaptic architecture. The present set of experiments investigates the influence of androgens on the development of SNB dendritic morphology. In normal males, SNB dendritic growth is biphasic, reaching exuberant lengths by the fourth postnatal week and then retracting to adult lengths by 7 weeks of age. This dendritic growth is androgen dependent--males castrated on postnatal day (P) 7 and given daily injections of testosterone propionate (TP) had exuberant dendritic lengths similar to those of normal males; dendritic length in oil-treated males remained at P7 levels. The early exuberant dendritic length was retained in TP-treated males through P49. The retraction of SNB dendrites after P28 is also influenced by androgens. Males castrated at P28 and given testosterone implants retained exuberant dendritic length at P49; blank-implanted males had significantly shorter dendritic lengths by P70. These results suggest that androgens are necessary for the early exuberant growth of SNB dendrites. Furthermore, the subsequent retraction of SNB dendrites may be halted when testosterone titers reach a critical level during puberty, stabilizing their adult length.